Plan de emprendimiento audiovisual: largometraje de ficción Augusto - Manco Otiniano, José Andrés (2023)
Augusto is a fiction feature film project of black humor genre which is in the development phase and already has a finished film script. Originality is the main attribute in this Project, which seeks to build its own space within Peruvian cinema thanks to its narrative qualities, such as the use of temporality, diction and the construction of its characters. Also with a production design that reflects a different view of Lima, less gray and more surreal. On the other hand, the focus of the narrative is more on the individual, the hero or antihero than a political or social reflection. In addition, it seeks to incorporate plastic art and Peruvian music into the production proposal The plot of the film is about Augusto, a frustrated accountant and artist who has one day to save his marriage but must make the right decision. That same day, two assassins, Pedro and Juan, have the mission to kill him but they find that there is more than one Augusto on their way, three to be exact and all three are the same person. On this day, in the city of Lima, chance and destiny will play an important role in achieving the goals of Augusto, Pedro and Juan. Thanks to the financing plan, an initial o S/.30,000 is needed to able to materialize this project in a storyboard, in a teaser, etc. The total realizations of this project is valued at S/ 1,070,399 and the ambition is that it be produced with Peruvian capital and in the city of Lima, for which financing will be sought in the contexts of the Ministry of Culture and in private companies. The objective of this document is to demonstrate the viability of this Project, not only for its originality, the use of black humor or the proposed artistic invoice but also thanks to the growth of Peruvian cinema in the world. The attributes of this Project translate into opportunities to take it to festivals that would reinforce its prestige, accompanied by a marketing strategy that seeks to generate visibility through social networks. Influencers and derived work from the film will be used to ultimately guarantee it profitability in the exhibition in the different windows proposed for this project.